3D‐Printed Coaxial Fibers for Integrated Wearable Sensor Skin. Issue 10 (20th August 2019) - Gao, Yang; Yu, Guohui; Shu, Tao; Chen, Yanqiu; Yang, Wenzhen; Liu, Yu; Long, Jing; Xiong, Wei; Xuan, Fuzhen
Abstract: Coaxial 3D printing technology, with its advantages of scalability and controllability, is applied in research to develop integrated wearable sensors composed of pressure sensor arrays and strain sensors. In order to improve the performance of the pressure sensor array, microstructures molded from sandpaper are introduced into the contact interface of the extruded fibers, resulting in a sensitivity (defined as the ratio of capacitance change to the change of applied pressure) of 0.562 kPa −1, a response/relaxation time of 230 ms, and a high durability. The printed strain sensor has a sensitivity (defined as the ratio of resistance change to the change of applied strain) of 11.8 and a good stability for 10 000 cycles. The high‐performance pressure sensor array and strain sensors give the integrated device the ability to detect various mechanical stimuli such as pressing, bending, twisting, and shear forces, showing potential application in the field of electronic skin. Abstract : A high‐performance integrated sensor array incorporating pressure and strain sensors is fabricated using coaxial 3D‐printed technique. This integrated sensor can detect various external stimuli, and could be applied to construct a wearable sensor skin.